CULTURAL SIGNS AND SYMBOLS AS A LINGUISTIC RESOURCE FOR IMPROVING STUDENTS’ PHRASEOLOGICAL COMPETENCE (Ustozlar uchun, 2025)
This paper explores the role of cultural signs and symbols as essential linguistic resources in enhancing students’ phraseological competence. It argues that idioms, proverbs, and other fixed expressions cannot be effectively learned without understanding the cultural meanings embedded within them. Drawing on theoretical perspectives from cultural linguistics, semiotics, and cognitive linguistics, the study emphasizes that cultural symbols provide the conceptual and emotional context that shapes phraseological meaning and use. Through the analysis of symbolic systems such as color, animal, religious, and body part metaphors, the paper highlights how different cultures encode distinct worldviews in their phraseological inventories. Furthermore, it proposes a cultural-symbolic approach to teaching phraseology that integrates etymological explanation, cross-cultural comparison, visual representation, and experiential learning. Such pedagogical practices not only enhance learners’ retention and appropriate use of idiomatic language but also foster intercultural awareness and communicative competence. The findings underline the necessity of viewing phraseological instruction as a culturally grounded process that connects linguistic knowledge with cultural understanding.Keywords: cultural symbols, phraseological competence, idioms, language teaching, intercultural competence, cognitive linguistics.